Analisis Pergerakan Harga Saham Emiten Sawit Terindeks Saham Syariah Indonesia Saat Larangan Ekspor CPO - Achmad Hidayat; Eja Armaz Hardi; Sucipto Sucipto; Zeni Sunarti (ITB AAS INDONESIA Surakarta, 2023)
This study raises the issue of the policy of banning CPO exports in influencing stock price movements of palm oil issuers listed on Indonesian sharia stock index. This study aims as reading material for technical analysis in making decisions to invest in Islamic stocks, especially palm oil issuers listed on the Indonesia Stock Exchange. The research method used is qualitative method, namely by data analysis through data reduction, data presentation and conclusion drawing. As a result, four of the seven oil palm issuers listed on ISSI experienced a decline in the CPO export ban policy period, while the others were stagnant, increased and fluctuated. Thus, it can be concluded that this policy affects the share price movements of palm oil issuers in the Indonesian Sharia Stock Index (ISSI).